2016
DOI: 10.1017/s0007485316000250
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal phenology and abundance ofLeucopis argenticollis, Leucopis piniperda(Diptera: Chamaemyiidae),Laricobius nigrinus(Coleoptera: Deridontidae) andAdelges tsugae(Hemiptera: Adelgidae) in the Pacific Northwest USA

Abstract: Adelges tsugae infested western hemlock trees were sampled periodically for 1 year at two locations in Oregon and Washington to compare the phenology and abundance of three associated predators (Leucopis argenticollis, Leucopis piniperda, and Laricobius nigrinus) and their host. On each sample date, two 3-10 cm long terminal twigs were collected from each tree and brought to the laboratory to count all life stages of A. tsugae and the three predators. Peak larval abundance of Leucopis spp. and La. nigrinus coi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 9 publications
0
19
0
Order By: Relevance
“…These Leucopis species have not been reported on A. tsugae in the eastern United States of America, and eastern and western lineages of both Leucopis species have distinct genotypes that appear to specialise on different adelgid species. The western strains are currently being evaluated and released as biological control agents for A. tsugae (Ross et al 2010;Grubin et al 2011;Kohler et al 2016;Motley et al 2017;Havill et al 2018). The current study shows that both Leucopis species are present in southwestern Virginia prior to release of the western lineages, which may aid establishment and ease ecological concerns regarding the introduction of foreign organisms to a new ecosystem.…”
Section: Discussionmentioning
confidence: 60%
“…These Leucopis species have not been reported on A. tsugae in the eastern United States of America, and eastern and western lineages of both Leucopis species have distinct genotypes that appear to specialise on different adelgid species. The western strains are currently being evaluated and released as biological control agents for A. tsugae (Ross et al 2010;Grubin et al 2011;Kohler et al 2016;Motley et al 2017;Havill et al 2018). The current study shows that both Leucopis species are present in southwestern Virginia prior to release of the western lineages, which may aid establishment and ease ecological concerns regarding the introduction of foreign organisms to a new ecosystem.…”
Section: Discussionmentioning
confidence: 60%
“…to be 2.3–3.5 times more abundant than La. nigrinus (Kohler et al ., 2016). However, the earlier study reported data collected at only two sites, one in Oregon and one in Washington.…”
Section: Discussionmentioning
confidence: 99%
“…larvae feed on the egg stage of both A. tsugae generations while La. nigrinus larvae feed only on the egg stage of the first adelgid generation (Kohler et al ., 2016).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because A. tsugae has two generations per year in its invaded range, it is critical that biological control efforts address both. Kohler et al (2016) found that Leucopis spp. exhibit peak abundances coinciding with both A. tsugae progrediens and sistens egg stages in the PNW.…”
Section: Discussionmentioning
confidence: 99%